2002
DOI: 10.1016/s1010-7940(02)00242-7
|View full text |Cite
|
Sign up to set email alerts
|

Completion pneumonectomy for non-small cell lung cancer: experience with 59 cases

Abstract: Completion pneumonectomy for non-small cell lung cancer is a safe surgical procedure in experienced hands; long-term survival is acceptable and the best results are obtained for stage I lung cancer. Distinction between second primary lung cancer and recurrence failed to demonstrate a prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
3
9
1
Order By: Relevance
“…However, the overall postoperative mortality rate of 11.6% in our study is consistent with recently reported rates of 2.6-20.9% [2,5,6,[8][9][10][11][12][13][14][15][16][17][18][19][20] (Table 3). Thus, postoperative mortality is usually higher after CP than after standard pneumonectomy [1,9].…”
Section: Discussionsupporting
confidence: 92%
“…However, the overall postoperative mortality rate of 11.6% in our study is consistent with recently reported rates of 2.6-20.9% [2,5,6,[8][9][10][11][12][13][14][15][16][17][18][19][20] (Table 3). Thus, postoperative mortality is usually higher after CP than after standard pneumonectomy [1,9].…”
Section: Discussionsupporting
confidence: 92%
“…Some reports have suggested that patients with a second primary lung cancer have a more favorable prognosis than patients with locally recurrent or metastatic disease (13-15). However, other reports did not reveal a significantly different survival between patients operated on for a second primary lung cancer or those patients operated on for locally recurrent or metastatic disease (4, 5, 8, 9). Our data showed that the 5-yr survival rates were not different between second primary lung cancer and the possible second primary or metastatic lung cancer.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, some researchers have insisted an aggressive surgical approach, whenever possible, as the survival rate after surgery is quite good (1-7). On the other hand, many doubts have been expressed concerning the utility of repeated surgery for recurrent lung cancer, as it is associated with a poor overall survival (8, 9). …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][9][10][11][12][13][14][15][16][17] The overall 30-day mortality and late mortality rates of the current series were 14.8% and 22%, respectively, and the non-complication group had a much higher rate of mortality than the other group, although this was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…McGovern et al [2] 113 12.4 9.4 27.6 38.1 11.7 Van Schil et al [15] 19 15.8 10.5 Gregoire et al [3] [16] 66 7.6 53 7.6 Terzi et al [17] 59 3.4 3.4 30 Miller et al [14] 115 20.9 17.6 26.3 62.6 7 Guggino et al [13] 55…”
Section: Study No Overall Mortality (%) Malignant (%) Benign (%) Overmentioning
confidence: 99%